Direct electrochemical deposition of polyaniline nanowire array on reduced graphene oxide modified graphite electrode for direct electron transfer biocatalysis. Issue 113 (30th October 2015) - Xia, Lin; Xia, Jianfei; Wang, Zonghua
Abstract : Direct electron transfer biocatalysis was achieved via electrochemically produced ordered PANI nanowire array on reduced graphene oxide modified graphite electrodes. Abstract : A highly ordered polyaniline (PANI) nanowire array is produced via a one-step template-free electrochemical approach on reduced graphene oxide (RGO) modified graphite electrode (GE). Direct electron transfer (DET) between glucose oxidase (GOx) and the electrode is achieved by using the PANI nanowire array with the immobilization of GOx. The DET based biocatalysis application of the as fabricated GOx/PANI/RGO/GE electrode has been demonstrated. The as-fabricated glucose sensor exhibits a very rapid response time (<3 s), a linear response to glucose in the concentration range of 0.1–8.5 mM, a sensitivity of 12.3 μA mM −1 cm −2, a low detection limit of 0.7 μM and good anti-interference ability. The as assembled glucose biofuel cell which uses GOx/PANI/RGO/GE as a bioanode and an electrochemically controlled cathode shows a maximum power output of 115.4 μW cm −2 .